Pengaruh Penggunaan Media Audiovisual Pada Pembelajaran Pendidikan Agama Islam (PAI) di SMK Negeri 2 Gowa - Risnawati, Risnawati; Hartini, Hartini; Deriwanto, Deriwanto (Program Studi Pendidikan Agama Islam Universitas Muhammadiyah Kendari, 2024)
The learning process is a communication process between teachers and students through verbal language as the main medium for delivering learning material. Under these conditions, the learning process is very dependent on the teacher as a learning resource and source of information. However, not all lesson materials can be presented directly by the teacher. However, teachers can use various kinds of tools in delivering learning material. Learning aids are what is meant by media or learning aids. In PAI learning, so that the learning material provided is more easily understood by students, media is needed that helps the delivery process. Through the media, it is hoped that there will be the same perception between teachers and students. Moreover, Islamic religious education is very important for human life, especially in achieving inner peace and mental health. Audiovisual media can be used as an alternative in learning Islamic Religious Education